Biotechnological processes as means to increase the accessibility and antioxidant activity of phenolic compounds from bread wheat and spelt grains - Mencin, Marjeta (Acta agriculturae Slovenica, 2024)
Cereal grains, especially bran, are a rich source of phenolic compounds with antioxidant activity. The potential positive effects of phenolics from whole grains of spelt and bread wheat on human health are limited by the poor bioaccessibility and bioavailability of their bound phenolics. Studies have shown that biotechnological processes (germination/fermentation/enzymatic treatment) are an effective strategy for improving the release of bound phenolics from the cell wall matrix of cereal grains. In this review article, the effects of biotechnological processes on the composition, antioxidant activity and bioaccessibility of phenolics from spelt and bread wheat grains are discussed in detail. Existing research indicates the presence of a different phenolics in spelt and bread wheat grains, making whole grains excellent for improving nutritional value of products. It has been shown that biotechnological processes can effectively increase the content of bioaccessible and bioavailable phenolics in cereal grains, which enables improved in vitro antioxidant activity. Currently, there is a lack of in vivo studies to confirm the findings obtained in vitro, so in vivo studies to determine the biological activity of phenolic compounds from pre-treated grains will be crucial in the future.
Keywords: antioksidanti; encimi; kemija okolja; žita